An exploratory investigation on spatiotemporal parameters, margins of stability, and their interaction in bilateral vestibulopathy - Nolan Herssens (Nature Portfolio, 2021)
Abstract Integration of accurate vestibular, visual, and proprioceptive information is crucial in managing the centre of mass in relation to the base of support during gait. Therefore, bilateral loss of peripheral vestibular function can be highly debilitating when performing activities of daily life. To further investigate the influence of an impaired peripheral vestibular system on gait stability, spatiotemporal parameters, step-to-step variability, and mechanical stability parameters were examined in 20 patients with bilateral vestibulopathy and 20 matched healthy controls during preferred overground walking. Additionally, using a partial least squares analysis the relationship between spatiotemporal parameters of gait and the margins of stability was explored in both groups. Patients with bilateral vestibulopathy showed an increased cadence compared to healthy controls (121 ± 9 vs 115 ± 8 steps/min; p = 0.02; d = 0.77). In addition, although not significant (p = 0.07), a moderate effect size (d = 0.60) was found for step width variability (Coefficient of Variation (%); Bilateral vestibulopathy: 19 ± 11%; Healthy controls: 13 ± 5%). Results of the partial least squares analysis suggest that patients with peripheral vestibular failure implement a different balance control strategy. Instead of altering the step parameters, as is the case in healthy controls, they use the single and double support phases to control the state of the centre of mass to improve the mechanical stability.